Nordkoreanske migranter i Kina. Konversion og socialt pres. - Læborg, Mette Hee (Religionsvidenskabeligt Tidsskrift, 2015)
Since the 1980s coercive persuasion has been scrutinized by sociologists in response to the preceeding discourse on supposed 'brainwashing' methods claimed to be utilized by new religious movements. The sociological consensus was that ‘brainwashing' and coercion rarely occur in religious conversion but this debate is revoked in light of Christian organizations' involvement with North Koreans in China. In China, North Koreans live under stressful conditions as illegal migrants exposed to criminal actions, while living under the threat of deportation. Christian organizations provide shelter, security and organize plights to a third country, if desired and possible, thus having a humanitarian functionality. The paper will argue that North Koreans in China, convert under grave social pressures as a result of well-organized religious groups, their availability, and social forces from the external world.